The Effectiveness of Gamal (Gliricidia sepium) Leaf Coconut Oil as a Treatment for Scabies and Acne among Students in Islamic Boarding Schools in East Java Province - Qurrota'Ayun, Henny; Sulika, Erni; Utami, Sri (Jurnal Biologi Tropis, 2025)
Skin diseases remain a significant public health issue in Indonesia, especially in Islamic boarding schools where students live communally in densely populated environments. This study aimed to evaluate the effectiveness of Gamal (Gliricidia sepium) leaf coconut oil as a natural therapy for scabies and acne among students in an Islamic boarding school in East Java Province. The research used a quantitative descriptive–experimental approach with a one-group pre-test and post-test design, involving 40 students clinically diagnosed with scabies and acne. All respondents received topical treatment using Gamal leaf coconut oil, prepared through a simple maceration process with Virgin Coconut Oil as the base. The intervention was carried out twice daily for five consecutive days, with clinical observations conducted before and after treatment. The results showed that 38 of 40 participants (90.48%) recovered completely, while 2 participants (9.52%) had mild remaining symptoms. The high recovery rate is attributed to the synergistic effect of bioactive compounds in Gliricidia sepium including flavonoids, tannins, saponins, and coumarins which exhibit antibacterial, antifungal, antiparasitic, and anti-inflammatory properties. The lipid content of coconut oil also contributes to skin regeneration and moisture restoration. This study concludes that Gamal leaf coconut oil is an effective, safe, and affordable herbal alternative for managing common skin infections in boarding schools. The findings also support the concept of community-based health independence through the utilization of locally available medicinal plants. Infections in boarding schools. Moreover, it supports the development of community-based health independence through the utilization of local bioresources.